Determinants of Long-Acting and Permanent Methods (LAPMS) of contraception use in Jambi Province, Indonesia - Hardiani Hardiani; Dwi Hastuti; Islakhiyah Islakhiyah; Junaidi Junaidi (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2020)
The use of long-acting and permanent methods of contraception (LAPMs) by couples of reproductive age in Jambi Province is still comparatively low. Long-term contraception users were only 18.26 percent in 2018. Based on these, the objective of the study is to analyze as follows: 1) the determinants of LAPMs and non-LAPMs used by couples of reproductive age; 2) the relationship between couples of reproductive age and use of LAPMs. Data is obtained from the 2018 Performance Monitoring and Accountability of Population, Family Planning, and Family Development programs. Data were analyzed using binary logistic regression, One-way ANOVA and Chi-Square Test. The results of the analysis found that the determinants of LAPM and non-LAPM selection by couples of reproductive age are woman’s educational attainment, woman’s employment status, the difference between ideal and actual number of surviving children, the desire for more children, the knowledge of contraceptive methods, economic conditions, and urban-rural residence. Furthermore, the characteristics of couples of reproductive age significantly related to the LAPM choice include woman’s age, woman’s educational attainment, the actual number of surviving children, the difference between ideal and actual number of surviving children, the desire for more children, the knowledge of contraceptive methods, economic conditions, and urban-rural residence.